Effectiveness Of E-Learning To Student Learning Satisfaction: A Literature Review - Nasiatin, Titin; Sansuwito, Tukimin Bin; Dioso, Regidor III (International Journal of Health Sciences, 2023)
Introduction: E-learning is acquiring knowledge and skills using the Internet, offering learners a versatile and individualized medium for education. It is a novel method of providing high-quality educational services to students through electronic means to enhance their knowledge, abilities, and consistency. Higher education institutions globally are increasingly using several forms of e-learning. Conversely, through engagement, e-learning has secured the improvement of learning abilities, knowledge, and excellence. Material and Methods: This study constitutes a comprehensive examination of the current body of literature. The subject matter, comprising publications published between 2018 and 2023, was selected from various internet sources, such as Science Direct, PubMed, and Google Scholar. We employed the PRISMA methodology to analyze the literature review systematically. Results: Following a comprehensive evaluation of 14 suitable papers, only 10 of the 183 articles chosen for analysis could be analyzed. Evidence suggests that e-learning can facilitate a fresh comprehension of the essential aspects of effective learning methodologies. Conclusion: According to the literature research findings, it was discovered that the e-learning model affects learning satisfaction, which is simultaneous with its influence. The level of contentment that students have with the outcomes of their e-learning experiences can be a primary measure of the quality of education provided in higher education.